2007
DOI: 10.1007/s10461-007-9271-2
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Anal Sex Among Female Drug Users: U.S. National Compared to Local Long Beach, California Data

Abstract: Receptive anal sex is a well-studied Human Immunodeficiency Virus (HIV) high-risk behavior among gay and bisexual men, yet previous research indicates that more women than men may be at risk from heterosexual anal sex (HAS). 1991-1996 data from the National Institute on Drug Abuse (NIDA) Cooperative Agreement (CA) were analyzed to model risk for women who reported having had HAS in the 30 days prior to interview. This model was then tested on recent data (2001-2006) collected on women in Long Beach, California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…In a nationally representative survey of adults in the United States lifetime AI was reported by about 40%, and AI in the past year by 20% of women aged 20-49 years. 1 Even higher prevalence has been recorded within sub-groups at “high risk” for HIV acquisition in the US: from 16% of substance-using women 2 and 19- 22% of women attending public STD clinics reporting AI within the past 3 months 3,4 and as high as 5 to 8% among female substance users in the past 30 days 5 . In South Africa, the prevalence of lifetime AI has been reported to be in excess of 40% among female sex workers 6 compared to only 5% among young women in the general population, 7 10% of women in the past 3 months in community settings 8 , and in the past month by 11% of women surveyed in alcohol serving establishments 9 – again with higher prevalence for “high risk groups”.…”
Section: Introductionmentioning
confidence: 99%
“…In a nationally representative survey of adults in the United States lifetime AI was reported by about 40%, and AI in the past year by 20% of women aged 20-49 years. 1 Even higher prevalence has been recorded within sub-groups at “high risk” for HIV acquisition in the US: from 16% of substance-using women 2 and 19- 22% of women attending public STD clinics reporting AI within the past 3 months 3,4 and as high as 5 to 8% among female substance users in the past 30 days 5 . In South Africa, the prevalence of lifetime AI has been reported to be in excess of 40% among female sex workers 6 compared to only 5% among young women in the general population, 7 10% of women in the past 3 months in community settings 8 , and in the past month by 11% of women surveyed in alcohol serving establishments 9 – again with higher prevalence for “high risk groups”.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates from the U.S. and U.K. suggest an average heterosexual anal intercourse prevalence of 11% (range = 2% to 39%) [1,2]. The highest rates have been found among female sex workers and patients at sexually transmitted infections (STI) clinics [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that women who trade sex for money or drugs are more likely to engage in anal sex. 22, 23 Anal sex has also been associated with injection drug use, 22 partner’s injection drug use, 18, 22 crack use, 18, 24 and amphetamine use. 23 …”
Section: Introductionmentioning
confidence: 99%